Contextual reinterpretation of quantum nonlocality - Khrennikov, Andrei 1958- (Cambridge University Press, 2024)
The quantum information revolution has had a huge impact not only on quantum technologies, including quantum computing and cryptography, but also on the foundations of quantum mechanics. This book presents the information viewpoint on the foundations of quantum physics by highlighting the role of complementarity and contextuality and coupling the ideas of the fathers of quantum mechanics, Bohr and Einstein, with the modern quantum information framework. The classical-quantum dilemma is resolved through an appeal to the Bild conception of scientific theories established in the 19th century by Hertz and Boltzmann. Bell inequalities are treated from the complementarity-contextuality viewpoint, supporting the attempts to discard nonlocality from quantum physics. Philosophical aspects of the topic are explored from a physicist's perspective, balancing accessibility with scientific rigour. This unique approach to quantum foundations will be of interest to graduates, Ph.D. students and researchers in fields ranging from quantum information to philosophy
Title from publisher's bibliographic system (viewed on 29 Nov 2024)
Introduction to quantum measurement theory -- Two faces of quantum nonlocality and two interpretations of quantum state -- Bohr's principle of complementarity and its contextual basis -- Information interpretations of quantum mechanics -- Quantum postulate as the seed of the complementarity principle -- Bell inequality : incompatibility versus nonlocality -- Classical entanglement : lessons from optics -- Original bell inequality and experiment -- Maximal violation of the original bell -- Contextual approach to probability and measurement -- Contextual structuring of classical and quantum physics -- Växjö interpretation -- Probabilistic entanglement of quantum observables -- Brownian motion : classical and semiclassical entanglement -- Bild conception for scientific theory -- Prequantum classical statistical field theory (PCSFT) -- QBism versus Ozawa's intersubjectivity theorem? -- Quantum-like modeling in biology, cognition, and decision making -- Noncommutative probability in classical systems
Keywords: Physics / Philosophy; Quantum theory